Zagreb Airport for the 2st Century - Pavlin, Stanislav; Malić, Adolf; Radačić, Željko (Promet - Traffic&Transportation, 2012)
Zagreb Airpor covers an area of 300 ha. The space is almostcompletely covered by vmious ailp011 facilities, buildingsand areas. The new role of the Zagreb Airport, the main airportof the independent Croatia is also the domicile of the air-ea/TierCroatia Airlines. It is also the main air base of the Croatian AirForce.Therefore, the capacities need to be expanded and modernised,especially regarding handling of passengers, luggage,cargo, mail and aircraft.The physical plan of the city of Zagreb includes ai1port developmentat the extended cun-entlocation. The first phase ofthe Master Plan includes the construction of a new passengerterminal and accompanying buildings and areas (tax.iways,aprons, parking lots, access roads ... ) and a long-te1m constructionof the second runway.The paper presents the expected traffic, necessary capacitiesand the physical plan regarding the Zagreb Ailp011 development.The implementation of sophisticated technical and technologicalsolutions is planned in the process of handling thepassengers, luggage, cargo, mail and aircraft.